Governing through uncertainty: a corpus-assisted discourse analysis of inflation and economic recovery in Indonesian policy communication - Tifani Yuliyana (Indonesian Journal of Language and Economic Discourse, 2026)
Background: Indonesia’s post-pandemic recovery unfolded amid inflationary pressure, exchange-rate volatility, geopolitical disruption, and persistent uncertainty, making official communication central to how economic risks and policy responses were publicly understood. Objective: This study examines how Indonesian policy institutions discursively governed uncertainty while communicating inflation management and economic recovery between 2022 and 2024. Method: Using corpus-assisted discourse analysis, this study analysed 21 primary policy communications from Bank Indonesia and the Coordinating Ministry for Economic Affairs, supported by three institutional reports and four BPS statistical releases, through keyword, collocation, concordance, modality, evaluation, transitivity, legitimation, and interdiscursivity analyses. Results: Findings show that uncertainty was predominantly externalised through global pressure, geopolitical tension, imported inflation, contagion, and risk, while domestic institutions retained agency as anticipatory managers. Forward-looking modality, projections, target horizons, and calibrated caution transformed uncertain futures into temporally bounded and administratively actionable policy problems. Implication: Institutional legitimacy was constructed through maintenance, strengthening, coordination, and a functional distinction between pro-stability and pro-growth instruments, although such coherence could obscure policy trade-offs. Novelty: This study contributes an integrated account of governing uncertainty by demonstrating how lexical patterning, temporal projection, and differentiated institutional agency jointly organise economic authority, expectation management, and public legitimation in Indonesian policy communication during a period of macroeconomic adjustment and contestation